2015
DOI: 10.1111/ced.12649
|View full text |Cite
|
Sign up to set email alerts
|

AKRT1gene mutation related to epidermolytic ichthyosis in a Chinese family

Abstract: We report a Chinese family with members affected by epidermolytic ichthyosis (EI), caused by KRT gene mutations. The proband was a 14-year-old boy who had simultaneous appearance of nephroblastoma and epidermolytic ichthyosis (EI). Both the patient and his mother exhibited the specific clinical and pathological manifestations of EI. We analysed all exons and flanking sequences of the KRT1 and KRT10 genes using PCR, and found that the proband and his mother had a G>C transition at nucleotide position 1432 in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Additionally, our study provides some possible candidate genes for horn development, including the KRT10 , KRT1, FMOD , free fatty acid receptor 4 ( FFAR4 ), serine protease 22 ( PRSS22 ), signal peptide, CUB domain, and EGF-like domain containing 2 ( SCUBE2 ), extracellular matrix protein 1 ( ECM1 ), and keratin 24 ( KRT24) genes. The genes KRT10 and KRT1 are expressed in keratinocytes during early differentiation [ 38 ], and their mutations cause epidermolytic hyperkeratosis [ 39 , 40 , 41 , 42 ]. In this study, KRT1 (FPKM = 3399) and KRT10 (FPKM = 2037) were found to be highly expressed in the horn buds, implying that KRT1 and KRT10 may regulate the keratinization of horn buds.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study provides some possible candidate genes for horn development, including the KRT10 , KRT1, FMOD , free fatty acid receptor 4 ( FFAR4 ), serine protease 22 ( PRSS22 ), signal peptide, CUB domain, and EGF-like domain containing 2 ( SCUBE2 ), extracellular matrix protein 1 ( ECM1 ), and keratin 24 ( KRT24) genes. The genes KRT10 and KRT1 are expressed in keratinocytes during early differentiation [ 38 ], and their mutations cause epidermolytic hyperkeratosis [ 39 , 40 , 41 , 42 ]. In this study, KRT1 (FPKM = 3399) and KRT10 (FPKM = 2037) were found to be highly expressed in the horn buds, implying that KRT1 and KRT10 may regulate the keratinization of horn buds.…”
Section: Discussionmentioning
confidence: 99%